Réponses

Meilleure réponse !
  • Utilisateur Brainly
2013-12-30T17:53:33+01:00
Z1=1+3i et z2=2-2i
donc
z1+z2=1+3i+2-2i
         =3+i
z2-2z1"barre"=2-2i-2(1-3i)
                   =4i
z1*z2=(1+3i)(2-2i)
          =2-2i+6i+6
          =8+4i
(z2)²=(2-2i)²
       =4-8i-4
       =-8i
(1-z1)(1+z2)=(-3i)(3-2i)
                 =-6-9i
2013-12-30T17:57:47+01:00
A) z1 + z2 
= (1+3i) + (2-2i)
= 1+ 3i + 2 -2i
= 3+ i

b) 2 - 2i - 2(1-3i)
= 2-2i - 2 +6i
= 4i

c)(1+3i)(2-2i)
= 2 - 2i +6i -6i²
= -6i² -4i +2 

d) (2-2i)²
= 2² -4i + 4i²
=4i²-4i+4

e) (1-(1+3i))(1+2-2i)
=  (-3i)(3-2i)
= -9i+6i²

Je ne suis pas sûre de moi 


Le C & le D sont faux mais merci quand même ;)